Securing corporate opportunities in Europe – comparative notes on monetary remedies and on the potential evolution of the remedial system. Issue 2 (3rd July 2018) - Corradi, Marco Claudio
ABSTRACT: Continental European jurisdictions have introduced corporate opportunities rules inspired by Anglo-American law. Despite a certain degree of homogeneity in substantive law, their monetary remedial systems still differ in common law and civil law jurisdictions. These differences matter because of the deterrence function connected to corporate opportunities remedies – deterrence being the core of fiduciary law. This article explains the divergences embedded in different legal traditions within a law and economics framework. It looks at potential developments of corporate opportunities remedies, drawing inspiration from a sample of European jurisdictions. Whereas UK law uses a vast array of remedies with high potential of deterrence and great flexibility in their application, civil law remedies are fewer, weaker and less flexible than the common law ones. However, the deterrence potential of civil law corporate opportunities remedies could be increased either through the introduction of criminal sanctions or future development of punitive damages doctrines.